Comparison of procurement of non-consulting services: public procurement rules-2008 Vs World Bank guidelines - Rahman, Md. Masudur (BARC University, 2018)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2016.